2016
DOI: 10.1539/joh.16-0055-oa
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of fall‐related occupational accidents in the workplace

Abstract: Objectives: This study aimed to examine effective assessment methods of falls in the workplace.Methods: There were 436 employees (305 males and 131 females) of electrical appliance manufacturers included in this study. In 2014, a baseline survey was conducted using the fall scores questionnaire and the self-check risk assessment of falls and other accidents in the workplace (physical function measurement and questionnaire). In 2015, the occurrence of falls in the past year was investigated. Multivariate logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In addition, several studies have already shown the association between exposure to noise with increased physical and mental stress. Combined, these risk factors increase the prevalence of road accidents (13,25,26) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have already shown the association between exposure to noise with increased physical and mental stress. Combined, these risk factors increase the prevalence of road accidents (13,25,26) .…”
Section: Discussionmentioning
confidence: 99%
“…The systematic literature revealed that agility is an advanced capability which allows different industries to gain competitive advantage and sustain their performance in the long term [12,[131][132][133][134]. It is also confirmed that companies want to build their agility capability through adopting Industry 4.0 technologies [135][136][137]. However, the authors argued whether adopting the Industry 4.0 technologies increase agility in a dynamic way [138,139], or whether adopting the Industry 4.0 technologies presents a change management challenge [140].…”
Section: Aspect Of Agility In Industry 40mentioning
confidence: 96%
“…The use of this tool is currently increasing in the Japanese manufacturing industry because it can safely measure the physical capabilities of older workers without the use of specialized measurement instruments. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%
“…Because farmers work in outdoor environments, with heavy use of their feet and legs, they may differ from other study populations. 17 , 18 Therefore, the purpose of the current study was to evaluate the relationship between physical capacity and experiences of occupational falls among middle‐aged and older Thai farmers using the Self‐Check Risk Assessment of Falls and Other Accidents in the Workplace tool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation